A study of learners' attitudes using TAM in a context-aware mobile learning environment. (27th July 2011) - Chen, Tzung-Shi; Chiu, Po-Sheng; Huang, Yueh-Ming; Chang, Cheng-Sian
This paper proposes a context-aware mobile learning (CAML) environment based on situated learning. Furthermore, we used the CAML to process an outdoor learning activity and evaluated the attitudes of learners. The participants involved in the experimental CAML-based outdoor learning activity were 70 five-grade students of an elementary school. The research data were collected through a questionnaire survey, constructed from these dimensions: learners' behavioural intentions (BITL), system quality (SQ), content quality and environment interaction. The results showed that SQ has high influence than perceived usefulness and ease of use, as well as has indirect influence on BITL. It could be inferred that learners have to perceive the system as useful before they are attracted and motivated to have learning behaviours. Thus, a good introduction of the learning system and the environment will help to enhance BITL.